2020
DOI: 10.1158/1535-7163.mct-19-0608
|View full text |Cite
|
Sign up to set email alerts
|

Epitope and Fc-Mediated Cross-linking, but Not High Affinity, Are Critical for Antitumor Activity of CD137 Agonist Antibody with Reduced Liver Toxicity

Abstract: CD137 (TNFRSF9, 4-1BB) agonist antibodies (mAb) have demonstrated potent antitumor activity with memory response while causing hepatotoxicity in mouse models. In clinical trials, the degrees of liver toxicity of anti-CD137 vary from grade 4 transaminitis (urelumab) to nonexistent (utomilumab). To exploit the antitumor potential of CD137 signaling, we identified a new class of CD137 agonist mAbs with strong antitumor potency without significant transaminitis in vivo compared with CD137 agonists previously repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…Accumulated clinical data was not promising for either antibody [53]. Efforts have been made to mitigate the liver toxicity and improve the efficacy of 4-1BB antibodies [52,54] by engineering the Fc portion of the antibody to eliminate binding to the activating FcγRs, including FcγRI, FcγRIIA, and FcγRIIIA, while retaining binding to the inhibitory Fc receptor FcγRIIB [52]. Alternatively, antibodies targeting different epitopes away from the ligand-binding sites may have better efficacy as well as safety profiles if they are IgG4, which have better binding affinity to FcγRIIB than IgG2, which only binds to FcγRIIA [54].…”
Section: Selection Of Igg Subclasses For Targets Expressed In Immune mentioning
confidence: 99%
“…Accumulated clinical data was not promising for either antibody [53]. Efforts have been made to mitigate the liver toxicity and improve the efficacy of 4-1BB antibodies [52,54] by engineering the Fc portion of the antibody to eliminate binding to the activating FcγRs, including FcγRI, FcγRIIA, and FcγRIIIA, while retaining binding to the inhibitory Fc receptor FcγRIIB [52]. Alternatively, antibodies targeting different epitopes away from the ligand-binding sites may have better efficacy as well as safety profiles if they are IgG4, which have better binding affinity to FcγRIIB than IgG2, which only binds to FcγRIIA [54].…”
Section: Selection Of Igg Subclasses For Targets Expressed In Immune mentioning
confidence: 99%
“…Efforts are underway to develop 4-1BB agonists with more favorable toxicity profiles that retain potent costimulatory capacities (80)(81)(82). In addition to the optimization of anti-4-1BB immunoglobulins (80,81), various formats of targeted 4-1BB agonists are being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have focused on the development of bispecific agonists promoting agonist localisation to the tumour microenvironment 56,58 , or have sought to understand the relative roles of Fab region binding versus FcR clustering. New preclinical studies of 4-1BB agonists have shown that strong anti-tumor efficacy can be generated whilst avoiding both 4-1BBL ligand-blocking and liver toxicity due to crosslinking 57,59 . One study has indicted that 4-1BB antibodies that are weak agonists from Fab binding alone, but require inhibitory Fcreceptor FcgRIIB-mediated crosslinking, retain anti-tumour activity in the absence of liver toxicity 57 .…”
Section: Discussionmentioning
confidence: 99%